ANALISIS DESKRIPTIF PENGGUNAAN INDIKATOR PERILAKU AMAN DALAM MENGUKUR TANGGUNG JAWAB SISWA SDN KEBALEN 07 - Yayah Nurfajriah; Husna Farhana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The assessment of responsibility in elementary school students tends to be subjective and lacks a foundation in observable behavioral indicators. Therefore, this study aims to describe the use of safe behavior indicators to measure student responsibility at SDN Kebalen 07. The study employs a qualitative approach using a descriptive method and a case study design. The research subjects consisted of the school principal, three classroom teachers (Grades IV, V, and VI), and six students. Data were collected through participant observation, semi-structured interviews, and documentation, then analyzed using the Miles and Huberman interactive model, involving data reduction, data display, and conclusion drawing. Data validity was ensured through source and technique triangulation. The results indicate that safe behavior indicators are effective for measuring student responsibility across five key aspects: adherence to safety rules, awareness of personal safety, responsibility toward the environment, concern for the safety of peers, and consistency in practicing safe behavior. These five indicators are evident in students' daily activities, such as complying with school regulations, maintaining environmental cleanliness, using school facilities responsibly, and reminding peers to behave safely. Thus, safe behavior can serve as an objective, contextual, and applicable indicator for measuring student responsibility and supporting character assessment in elementary schools.